2010
DOI: 10.1016/j.jnutbio.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin, an isoflavone, relaxes rat isolated aorta through endothelium-dependent and endothelium-independent pathways

Abstract: We evaluated the vasorelaxation effects of formononetin, an isoflavone/phytoestrogen found abundantly in Astragalus mongholicus Bunge, on rat isolated aorta and the underlying mechanisms involved. Cumulative administration of formononetin, genistein, daidzein and biochanin A relaxed phenylephrine-preconstricted aorta. Formononetin and biochanin A caused a similar magnitude of relaxation whereas daidzein was least potent. Mechanical removal of endothelium, L-NAME (100 microM) and methylene blue (10 microM) supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 24 publications
2
65
1
Order By: Relevance
“…L-NAME, a NOS inhibitor, inhibits the relaxation of formononetin, indicating that the vasorelaxant activity of formononetin is related to NO release. Similar findings are reported elsewhere [9] . The vasorelaxant effect of PGs is realized through increasing intracellular cAMP levels [35] .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…L-NAME, a NOS inhibitor, inhibits the relaxation of formononetin, indicating that the vasorelaxant activity of formononetin is related to NO release. Similar findings are reported elsewhere [9] . The vasorelaxant effect of PGs is realized through increasing intracellular cAMP levels [35] .…”
Section: Discussionsupporting
confidence: 93%
“…Our experimental results show that formononetin can relax the arteries pre-contracted by vasoconstrictors, indicating that the antihypertensive activities of formononetin maybe stem from the vasorelaxant activity. This is in concert with the previous findings that formononetin relaxes rat isolated aorta [9] and some isoflavones have vasorelaxant activities [15] . We have found that mesenteric artery is more sensitive to formononetin than abdominal aorta and renal artery in precontraction by phenylephrine, and meanwhile mesenteric artery is one of peripheral arteries which contribute more resistance than aorta in hypertension, and therefore we chose to study the vasorelaxant mechanism of formononetin on mesenteric artery.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations